TINGKAT ADVERSITY QUOTIENT MATEMATIS PADA MAHASISWA PROGRAM STUDI TADRIS MATEMATIKA IAIN CURUP - Septiana, Anisya (ARITHMETIC: Academic Journal of Math, 2019)
The purpose of this study was to determine the level of Adversity Quotient (AQ) students Tadris of the Mathematics Program of IAIN Curup. AQ is a person's ability to face the difficulties. Student difficulties faced can be in the form of assignments given by the lecturer, doing exams, and others. AQ level is categorized into three, namely quitter, camper, and climber. The subjects of this study were 33 students consisting of semesters II and IV. The research method used is a qualitative descriptive method. The process of collecting data is using a questionnaire. Data analysis using Microsoft Excel help. AQ score can be used as a reference for how a student responds to the difficulties faced. Based on the research that has been done, it is known that the AQ criteria that dominate are the camper categories as many as 27 (81.82%). Campers are a category of students who have tried, but the work that has been completed is not necessarily good. They are quite satisfied with what has been obtained, but their potential is not maximized. Therefore, they must be encouraged to improve their performance or efforts to be more maximal and more active and never give up in the face of difficulties.